2020
DOI: 10.1002/chem.202001470
|View full text |Cite
|
Sign up to set email alerts
|

Triarylborane‐Appended Anils and Boranils: Solid‐State Emission, Mechanofluorochromism, and Phosphorescence

Abstract: Herein, the design,s ynthesis, optical properties, and mechanofluorochromism characteristics of as eries of conjugates having covalently linked triarylborane (TAB) and anil/boranil units (TAB-anil: 1a-3a and TAB-boranil: 1-3)a re reported. The electronic interactions between TABa nd anil/ boranili n1a-3a and 1-3 were fine-tuned by changing the boryl moiety's positiono nt he phenyls pacer connecting the BMes 2 (Mes = mesityl)a nd anil/boranil units.Ab oryl moiety at the meta position(1a)o ft he phenyl spacers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 86 publications
(173 reference statements)
0
8
0
Order By: Relevance
“…Finally, intermolecular π-π stacking interactions (Figure 3b) are observed in the molecular packing of homochiral dimers. Note that the molecular geometry of H2 observed in its crystal structure may not necessarily be dominant in solution, as a careful analysis of the NOESY spectrum of this compound showed that the proton H 20 (of the CH=N imine) correlates with H 13 and H 14 (other extremity of the helicene) and with both H 1 and H 3 (see Figures S1.16a-b), thus suggesting the fast rotation around the C 2 À N (CÀ N 1 in Figure 3a) bound (in the NMR timescale). Similar conclusion holds also for H3, for which the analogous correlation of protons in the NOESY spectrum is seen (H 12 with H 1 , H 3 and H 4 , see Figures S1.37a-b).…”
Section: Synthesis and Structural Characterization Of Helicene-boranils H1-h3mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, intermolecular π-π stacking interactions (Figure 3b) are observed in the molecular packing of homochiral dimers. Note that the molecular geometry of H2 observed in its crystal structure may not necessarily be dominant in solution, as a careful analysis of the NOESY spectrum of this compound showed that the proton H 20 (of the CH=N imine) correlates with H 13 and H 14 (other extremity of the helicene) and with both H 1 and H 3 (see Figures S1.16a-b), thus suggesting the fast rotation around the C 2 À N (CÀ N 1 in Figure 3a) bound (in the NMR timescale). Similar conclusion holds also for H3, for which the analogous correlation of protons in the NOESY spectrum is seen (H 12 with H 1 , H 3 and H 4 , see Figures S1.37a-b).…”
Section: Synthesis and Structural Characterization Of Helicene-boranils H1-h3mentioning
confidence: 99%
“…The resulting novel helicenic boranils H1-H3 were then fully characterized by NMR and mass spectrometry (see Supporting Information). While the 1 H and 13 C NMR spectra display the typical, characteristic signals coming from both the helicene and boranil units, these compounds show very informative 11 B NMR and 19 F NMR (see Table 1 and Supporting Information). Indeed, H1 displays two chemically and magnetically equivalent fluorine atoms that resonate at À 136.5 ppm and demonstrate similar BÀ F coupling constants ( 1 J B-F = 17.3 Hz).…”
Section: Synthesis and Structural Characterization Of Helicene-boranils H1-h3mentioning
confidence: 99%
See 1 more Smart Citation
“…We have been involved in developing RTP materials for the last one decade. [33][34][35][72][73][74][75][76][77][78][79] As part of the ongoing program, we set to investigate the RTP characteristics of a series of simple triarylphosphines (1, 2, 3, and 4) and triarylphosphine oxides (5, 6, 7, and 8) to gain an understanding on how different are the lone pair electrons in R 3 P compared to arylphosphanediamines in the production of triplet excitons through np* transitions, and to understand the difference between R 3 P and R 3 P(O) based np* transitions in the production of triplet excitons. For this study, we synthesized a series of arylphosphines and arylphosphine oxides (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the intermolecular MFC (inter-MFC) based on reversible changes in molecular orientation and arrangement of dye molecules is superior in durability to the intramolecular MFC (intra-MFC) based on reversible changes in the chemical structures of dye molecules by cleavage and reconstruction of chemical bonds during the grinding–heating process, and thus, the inter-MFC is expected to be applicable to rewritable photoimaging and electroluminescence devices. 8–70 Among various types of fluorescent dyes possessing the mechanofluorochromic properties, donor–π–acceptor (D–π–A)-type fluorescent dyes composed of an electron-donating moiety (D) and an electron-withdrawing moiety (A) connected by a π-conjugated bridge exhibit intense photoabsorption and fluorescence emission properties based on the intramolecular charge transfer (ICT) excitation from the D moiety to the A moiety. 11–33 Thus, the dipole moments as well as photoabsorption ( i.e.…”
Section: Introductionmentioning
confidence: 99%